The effect of fuel injection equipment on the dispersed phase of water-in-diesel emulsions - Ismael, M.A. (Elsevier Ltd, 2018)
Water-in-diesel emulsions are known to lead to micro-explosions when exposed to high temperatures, thereby offering a technology that could improve the mixing of fuels with the ambient gas. The number and size distributions of the dispersed phase have a significant effect on both the long-term stability of the emulsion and the probability of micro-explosion inside an engine. Although the elevated pressures, temperatures, and shear found in high-pressure pumps and common-rail injector nozzles are likely to alter the properties of emulsions, the effect of these engine components on the injected emulsion are not known. To address this issue we sampled an emulsion at several locations within the injection system, from the fuel tank to the injector nozzle, and measured the evolution of the droplet size distribution of the emulsion's dispersed phase. We varied the water mass fraction (5, 10 and 15 by volume) of the emulsion and the injection pressure (500, 1000 and 1500 bar), imaged the samples using a high-resolution microscope and extracted the droplet size distribution using a purpose-built image processing algorithm. Our measurements reveal that the dispersed droplet sizes reduce significantly after the emulsion is compressed by the high-pressure fuel pump, and again after being injected through the nozzle's orifices. Additionally, the dispersed droplet sizes measured from the pump's return and injector return to the fuel tank were also smaller than the initial size, suggesting that the physical and calorific properties of the emulsion in the fuel tank can change significantly with time. Hence we propose that differences in injection equipment and engine testing duration may contribute to some of the disagreements in the literature regarding the effect of emulsified fuels on engine emissions and fuel efficiency. The engine performance and energy efficiency of vehicle fleets that use emulsified fuels will vary with engine running time, thus potentially inducing a drift in the engine performance and exhaust emissions. This investigation also suggests that, in order to be representative of actual injection conditions, fundamental studies of the micro-explosion of emulsion droplets should be performed using much smaller dispersed droplet sizes than those normally found in an unused emulsion. Â© 2018 Elsevier Ltd